PARTNERSHIP MODEL OF THE VILLAGE AUTHORITY IN DEVELOPING TOURISM SECTOR IN CONTO VILLAGE, BULUKERTO SUB-DISTRICT, WONOGIRI REGENCY - Nanda Praptiwi, Elista; Hilman, Yusuf Adam; Nasution, Robby Darwis; Widiyahseno, Bambang (Universitas Pendidikan Nasional, 2022)
The authority of Conto Village strives to develop the existing natural potentials by collaborating with investors, the community, and all associated actors. The purpose of this study is to describe the village partnership model taken by the authority in developing the village tourism, especially Conto village of tourism, Bulukerto Sub-District, Wonogiri Regency. The method applied in this study is a descriptive qualitative method with a purposive sampling technique. The instruments used are in-depth interviews and documentation by conducting interactive analysis. The Conto village authority and investors become the main actors in developing Goa Resi tourism with a profit-sharing arrangement model, whereas Pokdarwis and Mbah Sadiman are actors in developing Bukit Gendol tourism with a management contract cooperation model. In the other side, Soko Langit is managed privately, however in its development having a verbal profit-sharing arrangement with Pokdarwis. Banteng Vegetable Garden is managed by the owner of the garden and Pokdarwis through a profit-sharing arrangement, meanwhile the Coffee House is managed by BUMDes as well as the community, and developed by Pokdarwis with a management contract collaboration model. With the good cooperative activities from the youth and the farmers in Conto village, it will support the development of the natural potentials that expected to become the tourist attractions. In conclusion, the involvement of several actors is highly essential in conducting a cooperative partnership. Actors are the main key in cooperative relationships, thus in achieving a goal, each party shall collaborate to realize it.